Pathways Through Juvenile Justice: A System-Level Assessment of Cumulative Disadvantage in the Processing of Juvenile Offenders - Zane, Steven N. (Journal of quantitative criminology, 2022)
Objectives To test the cumulative disadvantage hypothesis—that system-level racial and ethnic disparities accumulate from intake to final disposition—by investigating relative and absolute disparities across different pathways through the juvenile justice system. Methods Using a sample of 95,670 juvenile court referrals across 140 counties in four states, the present study employed multinomial logistic regression to examine racial and ethnic disparities across 14 possible combinations of juvenile justice outcomes (i.e., pathways), ranked from least to most punitive. We then estimated predicted probabilities and marginal effects of race and ethnicity for each pathway. Results We found limited support for the cumulative disadvantage hypothesis. Racial and ethnic disparities were greatest for the most punitive pathways, but the findings do not point to extensive evidence of cumulative disadvantage. Specifically, neither relative nor absolute disparities accumulated from least to most punitive pathways, and some of the least punitive pathways were actually more likely for minority defendants. Conclusions The results underscore the need for more careful measurement and analysis of disadvantage and disparities in the criminal and juvenile justice systems. In particular, more attention should be paid to early outcomes such as detention, where large differences between racial and ethnic groups were observed, as well as to relative and absolute differences in processing outcomes.